Oxidized cellulose, nanocellulose and their dispersions
Patent Information
- Application Number
- JP2022116158
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-07-09
- Filing Date
- 2022-07-21
- Publication Date
- 2025-02-27
- Estimated Expiration
- 2041-07-09
AI Technical Summary
【0010】 本発明によれば、解繊性に優れた酸化セルロースを得ることができる。特に、本発明の酸化セルロースは、温和な条件で解繊処理を行った場合にも均一に微細化させることができ、易解繊性に優れている。
Smart Images

Figure 0007636723000001 
Figure 0007636723000002
Abstract
Description
[Technical field]
[0001] The present invention relates to oxidized cellulose, nanocellulose, and dispersions thereof. More specifically, the present invention relates to oxidized cellulose obtained by oxidizing a cellulosic raw material with an oxidizing agent, an oxidized cellulose dispersion containing the same, nanocellulose obtained by defibrating the oxidized cellulose, and a nanocellulose dispersion containing the same. [Background technology]
[0002] Various techniques have been proposed for producing nanocellulose materials such as cellulose nanofibers (hereinafter also referred to as "CNF") by oxidizing various cellulosic raw materials with an oxidizing agent and micronizing the resulting oxidized cellulose (see, for example, Patent Documents 1 and 2).
[0003] Patent Document 1 discloses that oxidized cellulose is obtained by oxidizing a cellulosic raw material using hypochlorous acid or a salt thereof as an oxidizing agent under high-concentration conditions of an effective chlorine concentration in the reaction system of 14 to 43% by mass. Patent Document 2 discloses that oxidized cellulose is obtained by oxidizing a cellulosic raw material using hypochlorous acid or a salt thereof as an oxidizing agent, setting the effective chlorine concentration in the reaction system to 6 to 14% by mass, and adjusting the pH to 5.0 to 14.0. In these techniques, the oxidation process is performed without using an N-oxyl compound such as 2,2,6,6-tetramethyl-1-piperidine-N-oxy radical (TEMPO) as a catalyst, so that no N-oxyl compound remains in the cellulose fiber, and therefore it is possible to produce nanocellulose materials while reducing the impact on the environment, etc. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2018 / 230354 [Patent Document 2] International Publication No. 2020 / 027307 Summary of the Invention [Problem to be solved by the invention]
[0005] Patent Documents 1 and 2 disclose a specific example of producing a nanocellulose material by pulverizing oxidized cellulose, in which a nanocellulose material is obtained through a defibration process by mechanical processing using an ultrasonic homogenizer. However, the above process has room for further improvement in terms of the energy required for defibration. In the production of nanocellulose materials, from the viewpoint of production costs, oxidized cellulose that has easy defibration properties that allow defibration even under mild processing conditions is required. In addition, in order to stably produce fine cellulose fibers or to obtain a nanocellulose material with high transparency with little light scattering in a dispersion medium, it is required that the defibration properties of the oxidized cellulose, which is in the state before the nanocellulose material is defibrated, be good.
[0006] The present invention has been made in view of the above circumstances, and a primary object of the present invention is to provide oxidized cellulose that has excellent defibrillation properties. [Means for solving the problem]
[0007] In order to solve the above problems, the present invention provides the following means. [1] Oxidized cellulose, which is an oxidation product of a cellulose-based raw material with hypochlorous acid or a salt thereof, and which is substantially free of N-oxyl compounds and has a degree of polymerization of 600 or less.
[0008] [2] The oxidized cellulose of [1], having a carboxyl group amount of 0.30 to 2.0 mmol / g. [3] The oxidized cellulose of [1] or [2], wherein the light transmittance of the nanocellulose aqueous dispersion obtained by defibrating an aqueous dispersion of the oxidized cellulose at a concentration of 0.1% by mass in a planetary centrifugal mixer at a revolution speed of 2000 rpm and a rotation speed of 800 rpm for 10 minutes is 60% or more. [4] Oxidized cellulose, which is an oxide of a cellulose-based raw material, wherein an aqueous dispersion of the oxidized cellulose having a concentration of 0.1% by mass is defibrated in a planetary centrifugal mixer at a revolution speed of 2000 rpm and a rotation speed of 800 rpm for 10 minutes, resulting in a nanocellulose aqueous dispersion having a light transmittance of 60% or more. [5] The oxidized cellulose according to [4], wherein the oxidized cellulose is an oxidation product of a cellulose-based raw material with hypochlorous acid or a salt thereof. [6] An oxidized cellulose dispersion in which any of the oxidized celluloses according to [1] to [5] is dispersed in a dispersion medium.
[0009] [7] Nanocellulose obtained by defibrating the oxidized cellulose according to any one of [1] to [6] and having an average fiber width of 1 to 200 nm. [8] Nanocellulose obtained by defibrating any of the oxidized celluloses according to [1] to [6] in a planetary centrifugal mixer at a revolution speed of 1,200 to 2,500 rpm and a rotation speed of 600 to 1,000 rpm for 3 to 15 minutes. [9] A nanocellulose dispersion in which the nanocellulose of [7] or [8] is dispersed in a dispersion medium. Effect of the Invention
[0010] According to the present invention, it is possible to obtain oxidized cellulose with excellent defibrability. In particular, the oxidized cellulose of the present invention can be uniformly finely divided even when defibration treatment is carried out under mild conditions, and has excellent easy defibrability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Oxidized cellulose The oxidized cellulose of the present disclosure (hereinafter also referred to as "the present oxidized cellulose") is fibrous cellulose obtained by oxidizing a cellulosic raw material with hypochlorous acid or a salt thereof, and is prior to defibration treatment. The present oxidized cellulose can also be said to be an oxide of the cellulosic raw material with hypochlorous acid or a salt thereof. The main component of plants is cellulose, and bundles of cellulose molecules are called cellulose microfibrils. The cellulose in the cellulosic raw material is also contained in the form of cellulose microfibrils. In addition, since "oxidized cellulose" is fibrous cellulose that has been oxidized as described above, it is also called "oxidized cellulose fiber."
[0012] Oxidized cellulose is substantially free of N-oxyl compounds because the cellulosic raw material is oxidized with hypochlorous acid or a salt thereof. In this specification, "substantially free of N-oxyl compounds" means that the oxidized cellulose does not contain any N-oxyl compounds, or the content of N-oxyl compounds is 2.0 ppm by mass or less, preferably 1.0 ppm by mass or less, based on the total amount of oxidized cellulose. In addition, when the content of N-oxyl compounds is increased from the cellulosic raw material by preferably 2.0 ppm by mass or less, more preferably 1.0 ppm by mass or less, it also means that the oxidized cellulose is "substantially free of N-oxyl compounds". By being substantially free of N-oxyl compounds, it is possible to prevent N-oxyl compounds, which are of concern for their impact on the environment and human body, from remaining in the oxidized cellulose. The content of N-oxyl compounds can be measured by known means. Known means include a method using a total nitrogen trace analyzer. Specifically, the nitrogen component derived from N-oxyl compounds in the oxidized cellulose can be measured as the amount of nitrogen using a total nitrogen trace analyzer (e.g., Mitsubishi Chemical Analytech Co., Ltd., device name: TN-2100H, etc.). The present oxidized cellulose will be described in detail below.
[0013] [Degree of polymerization] In a preferred embodiment of the present disclosure, the degree of polymerization of the present oxidized cellulose is 600 or less. If the degree of polymerization of the present oxidized cellulose exceeds 600, it tends to require a large amount of energy for defibration, and it tends not to be possible to exhibit sufficient easy defibration properties. In addition, if the degree of polymerization of the present oxidized cellulose exceeds 600, there will be a lot of oxidized cellulose that is insufficiently defibrated, and when this is finely defibrated into nanocellulose and dispersed in a dispersion medium, light scattering etc. will increase, and transparency may decrease. Furthermore, there will be a tendency for the size of the obtained nanocellulose to vary, resulting in non-uniform quality. For this reason, the viscosity of a slurry containing nanocellulose together with solid particles (hereinafter also referred to as "nanocellulose-containing slurry") will become unstable, and the handleability and coatability of the slurry may decrease. From the viewpoint of easy defibration properties, no lower limit is particularly set for the degree of polymerization of the present oxidized cellulose. However, if the degree of polymerization of the present oxidized cellulose is less than 50, the proportion of particulate cellulose rather than fibrous cellulose will be high, the quality of the slurry will be non-uniform, the viscosity will be unstable, and it will be difficult to obtain thixotropy, one of the characteristics of nanocellulose. From the above viewpoints, the degree of polymerization of the present oxidized cellulose is preferably 50-600.
[0014] The degree of polymerization of the present oxidized cellulose is more preferably 580 or less, even more preferably 560 or less, even more preferably 550 or less, still more preferably 500 or less, even more preferably 450 or less, and even more preferably 400 or less. From the viewpoint of improving the viscosity stability and coatability of the slurry, the lower limit of the degree of polymerization is more preferably 60 or more, even more preferably 70 or more, even more preferably 80 or more, even more preferably 90 or more, even more preferably 100 or more, even more preferably 110 or more, and particularly preferably 120 or more. A preferred range of the degree of polymerization can be determined by appropriately combining the above-mentioned upper and lower limits. The degree of polymerization of the present oxidized cellulose is more preferably 60 to 600, even more preferably 70 to 600, even more preferably 80 to 600, even more preferably 80 to 550, even more preferably 80 to 500, even more preferably 80 to 450, and particularly preferably 80 to 400.
[0015] The degree of polymerization of oxidized cellulose can be adjusted by changing the reaction time, reaction temperature, pH, and effective chlorine concentration of hypochlorous acid or its salt during the oxidation reaction. Specifically, since the degree of polymerization tends to decrease when the degree of oxidation is increased, a method of increasing the reaction time and / or reaction temperature of the oxidation can be used to decrease the degree of polymerization. As another method, the degree of polymerization of oxidized cellulose can be adjusted by the stirring conditions of the reaction system during the oxidation reaction. For example, under conditions in which the reaction system is sufficiently homogenized using a stirring blade or the like, the oxidation reaction proceeds smoothly and the degree of polymerization tends to decrease. On the other hand, under conditions in which the stirring of the reaction system is likely to be insufficient, such as stirring with a stirrer, the reaction tends to become non-uniform, making it difficult to sufficiently reduce the degree of polymerization of the cellulose fiber. The degree of polymerization of oxidized cellulose also tends to vary depending on the selection of the raw cellulose. For this reason, the degree of polymerization of oxidized cellulose can also be adjusted by selecting the cellulosic raw material. In this specification, the degree of polymerization of oxidized cellulose is the average degree of polymerization (viscosity average degree of polymerization) measured by a viscosity method. For details, follow the method described in the Examples below.
[0016] [Carboxy group amount] The amount of carboxy groups in the present oxidized cellulose is preferably 0.30 to 2.0 mmol / g. When the amount of carboxy groups is 0.30 mmol / g or more, sufficient easy defibration properties can be imparted to the oxidized cellulose. This makes it possible to obtain a nanocellulose-containing slurry with uniform quality even when defibration treatment is performed under mild conditions, and improves the viscosity stability, handleability, and coatability of the slurry. On the other hand, when the amount of carboxy groups is 2.0 mmol / g or less, excessive decomposition of cellulose during defibration treatment can be suppressed, and nanocellulose with a low ratio of particulate cellulose and uniform quality can be obtained. From this perspective, the amount of carboxy groups in the present oxidized cellulose is more preferably 0.35 mmol / g or more, even more preferably 0.40 mmol / g or more, even more preferably 0.42 mmol / g or more, even more preferably 0.50 mmol / g or more, even more preferably more than 0.50 mmol / g, and even more preferably 0.55 mmol / g or more. The upper limit of the amount of carboxyl groups is more preferably 1.5 mmol / g or less, even more preferably 1.2 mmol / g, even more preferably 1.0 mmol / g or less, and even more preferably 0.9 mmol / g. A preferred range of the amount of carboxyl groups can be determined by appropriately combining the above-mentioned upper and lower limits. The amount of carboxyl groups in the present oxidized cellulose is more preferably 0.35 to 2.0 mmol / g, even more preferably 0.35 to 1.5 mmol / g, even more preferably 0.40 to 1.5 mmol / g, even more preferably 0.50 to 1.2 mmol / g, even more preferably more than 0.50 to 1.2 mmol / g, and even more preferably 0.55 to 1.0 mmol / g.
[0017] The amount of carboxy groups (mmol / g) in oxidized cellulose is a value calculated using the following formula from the amount of sodium hydroxide (a) consumed in the neutralization stage of weak acid, where the change in electrical conductivity is gradual, after adding 0.1 M hydrochloric acid aqueous solution to an aqueous solution obtained by mixing oxidized cellulose with water to adjust the pH to 2.5, and then dropping 0.05 N aqueous sodium hydroxide solution and measuring the electrical conductivity until the pH reaches 11.0. For details, follow the method described in the Examples below. The amount of carboxy groups in oxidized cellulose can be adjusted by changing the reaction time, reaction temperature, pH of the reaction solution, etc. of the oxidation reaction. Amount of carboxyl group = a (ml) x 0.05 / mass of oxidized cellulose (g)
[0018] The present oxidized cellulose can be obtained, for example, by oxidizing a cellulosic raw material under conditions in which the available chlorine concentration of hypochlorous acid or a salt thereof in the reaction system is relatively high (for example, 14% by mass to 43% by mass).
[0019] The present oxidized cellulose preferably has a structure in which at least two of the hydroxyl groups of the glucopyranose ring constituting the cellulose have been oxidized, more specifically, the second and third hydroxyl groups of the glucopyranose ring have been oxidized and a carboxyl group has been introduced. It is also preferred that the hydroxyl group at the sixth position of the glucopyranose ring in the present oxidized cellulose is not oxidized and remains as a hydroxyl group. The position of the carboxyl group in the glucopyranose ring of the oxidized cellulose is determined by the presence of a carboxyl group in the glucopyranose ring of the oxidized cellulose. 13 It can be analyzed by C-NMR spectroscopy. The above solid 13 In the C-NMR spectrum, peaks corresponding to the carboxy groups at the second and third positions of the glucopyranose ring are observed, and thus it can be determined that the compound has an oxidized structure. In this case, the peaks corresponding to the carboxy groups at the second and third positions can be observed as broad peaks in the range of 165 ppm to 185 ppm. The broad peak here can be determined by the peak area ratio. That is, a baseline is drawn around the peak in the range of 165 ppm to 185 ppm in the NMR spectrum to determine the total area value, and then the area value is vertically divided at the peak top to determine the ratio of the two peak area values (larger area value / smaller area value). If the ratio of the peak area values is 1.2 or more, it can be said to be a broad peak. The presence or absence of the broad peak can be determined by the ratio of the length L of the baseline in the range of 165 ppm to 185 ppm to the length L' of the perpendicular line from the peak top to the baseline. That is, if the ratio L' / L is 0.1 or more, it can be determined that a broad peak is present. The ratio L' / L may be 0.2 or more, 0.3 or more, 0.4 or more, or 0.5 or more. The upper limit of the ratio L' / L is not particularly limited, but is usually 3.0 or less, 2.0 or less, or 1.0 or less.
[0020] In addition, the structure of the above-mentioned glucopyranose ring of this nanocellulose can also be determined by analysis in accordance with the method described in Sustainable Chem. Eng. 2020, 8, 48, 17800-17806.
[0021] The oxidized cellulose of the present disclosure has excellent defibrability. In particular, the oxidized cellulose of the present disclosure can be uniformly finely divided even when defibration treatment is performed under mild conditions, and has excellent easy defibrability. Furthermore, when the finely divided oxidized cellulose is mixed with inorganic particles such as pigments to form a slurry, the slurry viscosity is stable over time and the handling and coating properties are excellent. Furthermore, since it does not contain N-oxyl compounds, the impact on the environment, etc. can be reduced.
[0022] [Method of producing oxidized cellulose] Next, a method for producing the present oxidized cellulose will be described. The present oxidized cellulose can be produced by a method including a step of oxidizing a cellulosic raw material with hypochlorous acid or a salt thereof.
[0023] The cellulosic raw material is not particularly limited as long as it is a material mainly composed of cellulose, and examples thereof include pulp, natural cellulose, regenerated cellulose, and fine cellulose obtained by depolymerizing cellulose by mechanical treatment. As the cellulosic raw material, commercially available products such as crystalline cellulose made from pulp can be used as they are. In addition, unused biomass containing a large amount of cellulose components, such as soybean pulp pulp, may be used as the raw material. In addition, the cellulosic raw material may be treated in advance with an appropriate concentration of alkali in order to facilitate the penetration of the oxidizing agent used into the raw pulp.
[0024] Examples of hypochlorous acid or its salts used for the oxidation of cellulosic raw materials include hypochlorous acid water, sodium hypochlorite, potassium hypochlorite, calcium hypochlorite, and ammonium hypochlorite, etc. Among these, sodium hypochlorite is preferred from the viewpoint of ease of handling.
[0025] Methods for producing the present oxidized cellulose by oxidation of a cellulosic raw material include a method of mixing the cellulosic raw material with a reaction solution containing hypochlorous acid or a salt thereof. The reaction solution preferably contains water as a solvent, in terms of ease of handling and the reduced occurrence of side reactions. The available chlorine concentration of hypochlorous acid or a salt thereof in the reaction solution is preferably 6 to 43% by mass, more preferably 7 to 43% by mass, even more preferably 10 to 43% by mass, and even more preferably 14 to 43% by mass. When the available chlorine concentration of the reaction solution is within the above range, the amount of carboxy groups in the oxidized cellulose can be sufficiently increased, and defibration of the oxidized cellulose can be easily performed when obtaining nanocellulose.
[0026] From the viewpoint of efficiently increasing the amount of carboxy groups in the oxidized cellulose, the available chlorine concentration of the reaction liquid is more preferably 15% by mass or more, even more preferably 18% by mass or more, and even more preferably 20% by mass or more. Moreover, from the viewpoint of suppressing excessive decomposition of cellulose during defibration, the available chlorine concentration of the reaction liquid is more preferably 40% by mass or less, and even more preferably 38% by mass or less. The range of the available chlorine concentration of the reaction liquid can be an appropriate combination of the above-mentioned lower and upper limits. The range of the available chlorine concentration is more preferably 16 to 43% by mass, and even more preferably 18 to 40% by mass.
[0027] The effective chlorine concentration of hypochlorous acid or its salt is defined as follows. Hypochlorous acid is a weak acid that exists as an aqueous solution, and hypochlorite is a compound in which hydrogen of hypochlorous acid is replaced by other cations. For example, sodium hypochlorite, which is a hypochlorite, exists in a solvent (preferably in an aqueous solution), so the concentration is measured as the amount of effective chlorine in the solution, not the concentration of sodium hypochlorite. Here, for the effective chlorine of sodium hypochlorite, the oxidizing power of the divalent oxygen atom generated by the decomposition of sodium hypochlorite corresponds to the two atomic equivalents of monovalent chlorine, so that the bonded chlorine atom of sodium hypochlorite (NaClO) has the same oxidizing power as two atoms of unbonded chlorine (Cl2), and effective chlorine = 2 × (chlorine in NaClO). As a specific procedure for measurement, first, the sample is precisely weighed, water, potassium iodide and acetic acid are added, and the sample is left to stand, and the liberated iodine is titrated with a sodium thiosulfate solution using a starch aqueous solution as an indicator to measure the effective chlorine concentration.
[0028] The oxidation reaction of the cellulosic raw material with hypochlorous acid or a salt thereof is preferably carried out while adjusting the pH to the range of 5.0 to 14.0. In this range, the oxidation reaction of the cellulosic raw material can be sufficiently progressed, and the amount of carboxyl groups in the oxidized cellulose can be sufficiently increased. This makes it possible to easily defibrate the oxidized cellulose. The pH of the reaction system is more preferably 6.0 or higher, even more preferably 7.0 or higher, and even more preferably 8.0 or higher. The upper limit of the pH of the reaction system is more preferably 13.5 or lower, and even more preferably 13.0 or lower. The pH range of the reaction system is more preferably 7.0 to 14.0, and even more preferably 8.0 to 13.5.
[0029] Hereinafter, the method for producing the present oxidized cellulose will be further described using as an example the case where sodium hypochlorite is used as hypochlorous acid or a salt thereof.
[0030] When oxidizing a cellulosic raw material using sodium hypochlorite, the reaction liquid is preferably an aqueous sodium hypochlorite solution. Methods for adjusting the effective chlorine concentration of an aqueous sodium hypochlorite solution to a target concentration (for example, target concentration: 6% by mass to 43% by mass) include concentrating an aqueous sodium hypochlorite solution having a lower effective chlorine concentration than the target concentration, diluting an aqueous sodium hypochlorite solution having a higher effective chlorine concentration than the target concentration, and dissolving sodium hypochlorite crystals (for example, sodium hypochlorite pentahydrate) in a solvent. Among these, the method of diluting an aqueous sodium hypochlorite solution or dissolving sodium hypochlorite crystals in a solvent to adjust the effective chlorine concentration as an oxidizing agent is preferable because it causes less self-decomposition (i.e., less reduction in effective chlorine concentration) and makes it easy to adjust the effective chlorine concentration.
[0031] The method for mixing the cellulosic raw material and the sodium hypochlorite aqueous solution is not particularly limited, but from the viewpoint of ease of operation, it is preferable to add the cellulosic raw material to the sodium hypochlorite aqueous solution and mix them.
[0032] In order to efficiently proceed with the oxidation reaction of the cellulosic raw material, it is preferable to carry out the oxidation reaction while stirring the mixture of the cellulosic raw material and the aqueous sodium hypochlorite solution. Examples of the stirring method include a magnetic stirrer, a stirring rod, a stirrer with stirring blades (three-one motor), a homomixer, a dispersion type mixer, a homogenizer, and external circulation stirring. Among these, a method using one or more of shear type stirrers such as a homomixer and a homogenizer, a stirrer with stirring blades, and a dispersion type mixer is preferable, in that the oxidation reaction of the cellulosic raw material proceeds smoothly and the polymerization degree of the oxidized cellulose is easily adjusted to a predetermined value or less, and a method using a stirrer with stirring blades is particularly preferable. When a stirrer with stirring blades is used, a device equipped with known stirring blades such as a propeller blade, a paddle blade, or a turbine blade can be used as the stirrer. In addition, when a stirrer with stirring blades is used, it is preferable to carry out the stirring at a rotation speed of 50 to 300 rpm.
[0033] The reaction temperature in the oxidation reaction is preferably 15°C to 100°C, and more preferably 20°C to 90°C. During the reaction, the pH of the reaction system decreases as carboxyl groups are generated in the cellulosic raw material by the oxidation reaction. For this reason, from the viewpoint of efficiently proceeding with the oxidation reaction, it is preferable to add an alkaline agent (e.g., sodium hydroxide, etc.) or an acid (e.g., hydrochloric acid, etc.) to the reaction system and perform the oxidation reaction while adjusting the pH of the reaction system. The reaction time of the oxidation reaction can be set according to the degree of progress of the oxidation, but is preferably about 15 minutes to 50 hours. When the pH of the reaction system is set to 10 or more, it is preferable to set the reaction temperature to 30°C or more and / or the reaction time to 30 minutes or more.
[0034] The solution containing the oxidized cellulose obtained by the above reaction can be subjected to a known isolation treatment such as filtration, and further purified as necessary, to obtain oxidized cellulose as an oxide of a cellulose-based raw material with hypochlorous acid or a salt thereof. In order to improve the filterability and yield of the isolation treatment, an acid can be added to the solution containing the oxidized cellulose prior to the isolation treatment such as filtration, for example to adjust the pH to 4.0 or less, and at least a portion of the carboxyl groups produced by the oxidation can be converted into a salt form (-COO - X + :X + indicates positive ions such as sodium and lithium) to proton type (-COO - H + ) can be used. In the infrared absorption spectrum, the proton type has an absorption peak at 1720 cm -1 Nearby, the salt type is 1600cm -1 They can be distinguished from each other by the presence of peaks in their vicinity. The solution containing oxidized cellulose obtained by the above reaction may be subjected to defibration treatment as it is.
[0035] In the case where the pH of the solution containing oxidized cellulose is adjusted to 4.0 or less for the isolation treatment, in order to improve the handling property when the solution is used for the subsequent defibration treatment, for example, a base is added to adjust the pH to 6.0 or more, and at least a part of the carboxyl groups is converted to a salt type (-COO - X + :X + indicates a cation such as sodium or lithium). Moreover, a solution containing oxidized cellulose may be made into a composition containing oxidized cellulose by, for example, replacing the solvent. In the composition containing oxidized cellulose, for example, an alkaline condition of pH 10 or more is set, and at least a portion of the carboxyl groups are converted into a salt type (-COO - X + :X + indicates a cation such as sodium, lithium, etc.
[0036] The method for producing oxidized cellulose may further include a step of mixing the obtained oxidized cellulose with a compound having a modifying group in order to control the physical properties of the oxidized cellulose. The compound having a modifying group is not particularly limited as long as it has a modifying group capable of forming an ionic bond or a covalent bond with a carboxyl group or a hydroxyl group of the oxidized cellulose. Examples of compounds having a modifying group capable of forming an ionic bond include primary amines, secondary amines, tertiary amines, quaternary ammonium compounds, and phosphonium compounds. Examples of compounds having a modifying group capable of forming a covalent bond include alcohols, isocyanate compounds, and epoxy compounds. As described above, the present oxidized cellulose includes salt, proton, and modified forms. Nanocellulose obtained from the present oxidized cellulose also includes salt, proton, and modified forms.
[0037] The present oxidized cellulose may be in the form of a mixture with a dispersion medium. That is, one aspect of the present invention is an oxidized cellulose dispersion in which the present oxidized cellulose is dispersed in a dispersion medium. Examples of the dispersion medium include the same dispersion media as those described below.
[0038] Nanocellulose The nanocellulose of the present disclosure (hereinafter also referred to as "the present nanocellulose") can be obtained by oxidizing a cellulosic raw material with an oxidizing agent, and then defibrating the oxidized cellulose to produce nano-sized particles. That is, the present nanocellulose can be produced by a method including a step of oxidizing a cellulosic raw material with hypochlorous acid or a salt thereof, and a step of defibrating the oxidized cellulose obtained by the step. The oxidation step is as described above. In addition, since "nanocellulose" is a fibrous cellulose that has been finely divided from oxidized fibrous cellulose, it is also called "fine cellulose fiber."
[0039] Methods for defibrating oxidized cellulose include, for example, mechanical defibration, etc. Here, nanocellulose (hereinafter also referred to as nanocellulose) is a general term for cellulose that has been nanosized, and includes cellulose nanofibers, cellulose nanocrystals, etc.
[0040] Examples of methods for mechanical defibration include methods using various mixing and stirring devices such as a screw mixer, a paddle mixer, a disperser mixer, a turbine mixer, a homomixer under high speed rotation, a high pressure homogenizer, an ultra-high pressure homogenizer, a double cylindrical homogenizer, an ultrasonic homogenizer, a water current opposing collision type disperser, a beater, a disk type refiner, a conical type refiner, a double disk type refiner, a grinder, a single-shaft or multi-shaft kneader, a planetary centrifugal mixer, a vibration type mixer, etc. By treating the oxidized cellulose with one of these devices alone or in combination of two or more types, preferably in a dispersion medium, the oxidized cellulose can be nanosized to produce nanocellulose.
[0041] The defibration of the present oxidized cellulose may be carried out, for example, using a method using an ultra-high pressure homogenizer, since this allows efficient production of nanocellulose with a more advanced defibration. When defibration is carried out using an ultra-high pressure homogenizer, the pressure during the defibration treatment is preferably 100 MPa or more, more preferably 120 MPa or more, and even more preferably 150 MPa or more. The number of times of defibration treatment is not particularly limited, but from the viewpoint of sufficiently advancing defibration, it is preferably 2 times or more, and more preferably 3 times or more.
[0042] Because this oxidized cellulose has excellent defibrability, it can be sufficiently defibrated even when mild stirring is applied, for example, using a planetary centrifugal mixer or a vibration mixer, making it suitable for obtaining uniform nanocellulose.
[0043] The planetary centrifugal mixer is a device that mixes materials in a container by rotating and revolving the container into which the materials are put. The planetary centrifugal mixer can achieve gentler mixing because mixing is performed without using stirring blades. The revolution speed and rotation speed during mixing by the planetary centrifugal mixer can be set appropriately, for example, the revolution speed can be set to 400 to 3000 rpm and the rotation speed can be set to 200 to 1500 rpm. When using the planetary centrifugal mixer, it is preferable to perform the defibration process under the conditions of mixing for 3 to 15 minutes at a revolution speed of 1200 to 2500 rpm and a rotation speed of 600 to 1000 rpm, from the viewpoint of achieving gentle mixing while ensuring uniformity of quality. The revolution speed is more preferably 1500 to 2300 rpm, and the rotation speed is more preferably 700 to 950 rpm. When defibrating the oxidized cellulose using a planetary centrifugal mixer, the concentration of the oxidized cellulose aqueous dispersion used as the raw material may be appropriately adjusted, for example, to 0.01 to 1.0% by mass, and preferably 0.1 to 0.5% by mass.
[0044] An example of a vibration type agitator is a vortex mixer (touch mixer). In a vortex mixer, stirring is performed by forming a vortex in the liquid material in a container. With a vibration type agitator such as a vortex mixer, stirring is performed without using a stirring blade, so that gentler stirring can be realized. Furthermore, with a vibration type agitator such as a vortex mixer, gentle stirring can be realized with simple equipment, so that it is superior in terms of production equipment and production costs. The rotation speed of the vortex mixer is, for example, 600 to 3000 rpm, and it is preferable to perform the defibration treatment under stirring conditions of 3 to 15 minutes. When the present oxidized cellulose is defibrated with a vortex mixer, the concentration of the oxidized cellulose aqueous dispersion used as the material may be appropriately adjusted, but is, for example, 0.01 to 1.0 mass %, and preferably 0.1 to 0.5 mass %.
[0045] The defibration treatment is preferably carried out in a state where the oxidized cellulose is mixed with a dispersion medium. There are no particular limitations on the dispersion medium, and it can be appropriately selected depending on the purpose. Specific examples of the dispersion medium include water, alcohols, ethers, ketones, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethylsulfoxide. As the solvent, one of these may be used alone, or two or more may be used in combination.
[0046] Among the above dispersion media, examples of alcohols include methanol, ethanol, isopropanol, isobutanol, sec-butyl alcohol, tert-butyl alcohol, methyl cellosolve, ethylene glycol, and glycerin. Examples of ethers include ethylene glycol dimethyl ether, 1,4-dioxane, and tetrahydrofuran. Examples of ketones include acetone and methyl ethyl ketone.
[0047] By using an organic solvent as a dispersion medium during the defibration process, it becomes easier to isolate the oxidized cellulose and the nanocellulose obtained by defibrating it. In addition, since the nanocellulose is obtained dispersed in the organic solvent, it becomes easier to mix it with resins that dissolve in the organic solvent and the raw material monomers for the resins. The nanocellulose dispersion obtained by dispersing the nanocellulose obtained by defibration in a dispersion medium of water and / or an organic solvent can be used to mix with various components such as resins, rubbers, and solid particles.
[0048] [Average fiber width] The average fiber width of the nanocellulose is preferably 1 to 200 nm. In particular, the present oxidized cellulose is suitable in that it can obtain nanocellulose that is sufficiently nano-sized with an average fiber width of 1 to 20 nm, preferably 1 to 10 nm, and more preferably 1 to 5 nm, by defibration treatment. In addition, when the average fiber width of the nanocellulose is sufficiently small, such as 1 to 5 nm, the viscosity of the slurry containing this nanocellulose is stable, and the handling and coating properties are good. The average fiber width of the nanocellulose is more preferably 4.8 nm or less, even more preferably 4.5 nm or less, and even more preferably 4.2 nm or less. From the viewpoint of easy defibration, no lower limit of the average fiber width is particularly set. However, if the average fiber width is less than 1 nm, it becomes close to the form of a single cellulose molecule, and the quality of the nanocellulose is likely to be non-uniform. For this reason, the average fiber width is preferably 1 nm or more, and more preferably 1.5 nm or more.
[0049] [Average fiber length] The average fiber length of the nanocellulose is preferably 100 to 2000 nm, more preferably 100 to 1000 nm, even more preferably 100 to 500 nm, and still more preferably 100 to 400 nm.
[0050] Aspect Ratio In the present nanocellulose, the aspect ratio (average fiber length / average fiber width), which is expressed as the ratio of the average fiber width to the average fiber length, is preferably 20 to 200. The aspect ratio is more preferably 30 or more, and even more preferably 40 or more. Moreover, the aspect ratio is more preferably 180 or less, and even more preferably 150 or less.
[0051] The average fiber width and the average fiber length are values calculated by mixing nanocellulose and water so that the concentration of nanocellulose is approximately 1 to 10 ppm, naturally drying the sufficiently diluted cellulose water dispersion on a mica substrate, observing the shape of the nanocellulose using a scanning probe microscope, randomly selecting any number of fibers from the obtained image, setting the cross-sectional height of the shape image = fiber width, and setting the perimeter ÷ 2 = fiber length. Image processing software can be used to calculate such average fiber width and average fiber length. At this time, the image processing conditions are arbitrary, but even for the same image, the calculated values may differ depending on the image processing conditions. The range of the difference in value due to the image processing conditions is preferably within ±100 nm for the average fiber length. The range of the difference in value due to the conditions is preferably within ±10 nm for the average fiber width. A more detailed measurement method follows the method described in the examples below.
[0052] [Light transmittance] With this oxidized cellulose, defibration can proceed sufficiently even under mild defibration conditions, and nanocellulose with a sufficiently small fiber width can be obtained. Furthermore, because the obtained nanocellulose has a sufficiently small fiber width, when dispersed in a dispersion medium, there is little light scattering of the cellulose fibers, and the nanocellulose exhibits high light transmittance. Therefore, this nanocellulose can be effectively used in applications where transparency is required.
[0053] Specifically, the present oxidized cellulose is preferably a nanocellulose aqueous dispersion obtained by defibrating an aqueous dispersion of the oxidized cellulose at a concentration of 0.1% by mass in a planetary agitator at a revolution speed of 2000 rpm and a rotation speed of 800 rpm for 10 minutes, and the optical transmittance of the nanocellulose aqueous dispersion is preferably 60% or more. The optical transmittance of this nanocellulose aqueous dispersion is more preferably 70% or more, even more preferably 75% or more, and even more preferably 80% or more. The optical transmittance is a value at a wavelength of 660 nm measured by a spectrophotometer.
[0054] Furthermore, the present oxidized cellulose is preferably such that the light transmittance of a nanocellulose aqueous dispersion obtained by defibrating an aqueous dispersion of the oxidized cellulose at a concentration of 0.1% by mass in a vortex mixer at a rotation speed of 3000 rpm for 10 minutes exhibits a value of 60% or more. The light transmittance of this nanocellulose aqueous dispersion is more preferably 70% or more, even more preferably 75% or more, and even more preferably 80% or more.
[0055] The reason why the oxidized cellulose of the present disclosure has excellent defibrability (especially easy defibrability) and gives a high-quality slurry is unclear, but it is generally believed to be the following. Defibrification proceeds by breaking hydrogen bonds between cellulose microfibrils. In an oxidation treatment using hypochlorous acid or a salt thereof, a decrease in the degree of polymerization of microfibrils (i.e., shortening of cellulose molecular chains) occurs as the oxidation proceeds. When oxidation is performed with a relatively high concentration of hypochlorous acid or a salt thereof, the decrease in the degree of polymerization is more likely to proceed with an increase in the degree of oxidation compared to, for example, the TEMPO oxidation method. For this reason, in the present embodiment, the number of hydrogen bonds to be broken by defibration in each microfibril is reduced by the oxidation treatment, and furthermore, the amount of carboxyl groups increases as the oxidation proceeds, which strengthens the repulsive force between microfibrils and improves the defibrability of the oxidized cellulose. It is also believed that the improved defibrability of the oxidized cellulose has enabled the production of nanocellulose that can improve the viscosity stability, handling properties, and coatability of the slurry.
[0056] (Other embodiments) In another preferred embodiment of the present disclosure, oxidized cellulose is provided in which a cellulose-based raw material is oxidized with an oxidizing agent. This oxidized cellulose can also be called oxidized cellulose, which is an oxide of a cellulose-based raw material. The oxidized cellulose of this embodiment is obtained by defibrating a 0.1% by mass aqueous dispersion of the oxidized cellulose in a planetary agitator at a revolution speed of 2000 rpm and a rotation speed of 800 rpm for 10 minutes, and the optical transmittance of the nanocellulose aqueous dispersion is 60% or more.
[0057] In another preferred embodiment of the present disclosure, the oxidized cellulose has a light transmittance of 60% or more in a nanocellulose aqueous dispersion obtained by defibrating a 0.1% by mass aqueous dispersion of the oxidized cellulose in a vortex mixer at a rotation speed of 3,000 rpm for 10 minutes.
[0058] That is, with these other forms of oxidized cellulose, defibration proceeds sufficiently even under mild defibration conditions, and nanocellulose with a sufficiently small fiber width of about 1 to 5 nm can be obtained. Since the obtained nanocellulose has a sufficiently small fiber width, when dispersed in a dispersion medium, light scattering of the cellulose fibers is small and the nanocellulose shows high light transmittance. Therefore, it can be effectively used in applications where transparency is required. Furthermore, even if the defibration treatment is performed under mild conditions, the nanocellulose obtained by defibrating the above-mentioned other forms of oxidized cellulose can stabilize the viscosity of the slurry when it is made into a nanocellulose-containing slurry, and can improve the handleability and coatability of the slurry.
[0059] Examples of the oxidizing agent include halogens, hypochlorous acid or its salts, peroxides, etc. Among these, hypochlorous acid or its salts are preferable because they can obtain homogenized nanocellulose, have a low environmental impact, and are inexpensive. Hypochlorous acid or its salts are as described above.
[0060] The nanocellulose and nanocellulose dispersion containing the nanocellulose described above can be applied to various applications. Specifically, for example, it may be mixed with various materials (e.g., resin, fiber, rubber, etc.) as a reinforcing material and used, or it may be used as a thickener or dispersant in various applications (e.g., food, cosmetics, medical products, paints, inks, etc.). The nanocellulose dispersion can also be formed into a film and used as various sheets or films. The fields in which the present nanocellulose and the nanocellulose dispersion containing the same are applied are not particularly limited, and can be used in the manufacture of products in various fields such as automotive parts, machine parts, electrical appliances, electronic devices, cosmetics, medical products, building materials, daily necessities, stationery, etc. In addition, when nanocellulose and the nanocellulose dispersion containing the same are used as additives to a slurry containing inorganic particles such as pigments, it is preferable in that the viscosity stability, handling properties, and coating performance of the slurry can be improved. EXAMPLES
[0061] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the following, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".
[0062] (1) Production of oxidized cellulose and nanocellulose [Production Example 1] As a cellulose-based raw material, softwood pulp (Sigma-Aldrich, NIST RM 8495, bleached kraft pulp) was cut into 5 mm squares with scissors and processed at 25,000 rpm for 1 minute in an Osaka Chemical Wonder Blender WB-1 to mechanically defibrate the material into a cotton-like form. In a beaker, 350 g of sodium hypochlorite pentahydrate crystals with an effective chlorine concentration of 42% by mass were placed, and pure water was added and stirred to obtain an aqueous solution of sodium hypochlorite with an effective chlorine concentration of 21% by mass. 35% by mass of hydrochloric acid was added thereto and stirred to obtain an aqueous solution of pH 11.0. This aqueous solution of sodium hypochlorite was heated to 30°C in a thermostatic water bath while being stirred at 200 rpm using a propeller-type stirring blade in a stirrer manufactured by Shinto Scientific Co., Ltd. (Three-One Motor, BL600), and then 50 g of the mechanically defibrated softwood kraft pulp (carboxyl group amount: 0.05 mmol / g) was added. After the cellulosic raw material was supplied, the mixture was kept at 30°C in the same thermostatic water bath, and the pH during the reaction was adjusted to 11.0 by adding 48% by mass of sodium hydroxide. The mixture was stirred at 200 rpm for 30 minutes using a propeller-type stirring blade in the above-mentioned stirrer to carry out the oxidation reaction. After the reaction was completed, the product was subjected to solid-liquid separation by suction filtration using a PTFE membrane filter with a mesh size of 0.1 μm to obtain oxidized cellulose A. The obtained oxidized cellulose A was washed with pure water, and the amount of carboxy groups in the filtered product after washing (oxidized cellulose A) was measured, which was 0.45 mmol / g. Next, pure water was added to oxidized cellulose A to prepare a 0.1% dispersion, and this was processed for 10 minutes in mix mode using a Thinky Planetary Mixer "Awatori Rentaro ARE-310" at a revolution speed of 2000 rpm and a rotation speed of 800 rpm to obtain CNF aqueous dispersion A as a nanocellulose dispersion. In addition, the nitrogen components derived from N-oxyl compounds in oxidized cellulose A were measured as the amount of nitrogen using a total nitrogen trace analyzer (manufactured by Mitsubishi Chemical Analytech Co., Ltd., device name: TN-2100H), and the increase from the raw pulp was calculated, and was found to be less than 1 ppm.
[0063] The available chlorine concentration in the aqueous sodium hypochlorite solution was measured by the following method. (Measurement of available chlorine concentration in sodium hypochlorite solution) 0.582g of an aqueous solution of sodium hypochlorite pentahydrate crystals added to pure water was precisely measured, 50ml of pure water was added, 2g of potassium iodide and 10ml of acetic acid were added, and the solution was immediately sealed and left in a dark place for 15 minutes. After leaving it for 15 minutes, the liberated iodine was titrated with 0.1mol / L sodium thiosulfate solution (indicator: starch test solution), and the titration amount was 34.55ml. A blank test was performed separately to correct the amount, and 1ml of 0.1mol / L sodium thiosulfate solution corresponds to 3.545mgCl, so the available chlorine concentration in the sodium hypochlorite aqueous solution is 21% by mass.
[0064] The amount of carboxy groups in oxidized cellulose was measured by the following method. (Measurement of Carboxylic Acid Group Amount) To 60 ml of an oxidized cellulose aqueous dispersion in which the concentration of oxidized cellulose had been adjusted to 0.5% by mass, a 0.1 M aqueous hydrochloric acid solution was added to adjust the pH to 2.5, and then a 0.05 N aqueous sodium hydroxide solution was added dropwise and the electrical conductivity was measured until the pH reached 11.0. The amount of carboxyl groups (mmol / g) was calculated using the following formula from the amount of sodium hydroxide (a) consumed in the neutralization stage of the weak acid, where the change in electrical conductivity was gradual. Amount of carboxyl group = a (ml) x 0.05 / mass of oxidized cellulose (g)
[0065] [Production Example 2] Oxidized cellulose B and CNF aqueous dispersion B were obtained by treating under the same conditions as in Production Example 1, except that the reaction time in the oxidation reaction was 120 minutes. [Production Example 3] Oxidized cellulose C and CNF aqueous dispersion C were obtained by treating under the same conditions as in Production Example 1, except that the reaction time for the oxidation reaction was set to 120 minutes and the cellulose-based raw material was changed to powdered cellulose (VP-1) manufactured by TDI Corporation. [Production Example 4] Oxidized cellulose D and CNF aqueous dispersion D were obtained by treating under the same conditions as in Production Example 1, except that the oxidation reaction time was set to 120 minutes and the cellulose-based raw material was changed to powdered cellulose (KC Flock W-100GK) manufactured by Nippon Paper Industries Co., Ltd.
[0066] [Production Example 5] Oxidized cellulose E and CNF aqueous dispersion E were obtained by treating under the same conditions as in Production Example 1, except that the oxidation reaction time was 240 minutes. [Production Example 6] Oxidized cellulose F and CNF aqueous dispersion F were obtained by treating under the same conditions as in Production Example 1, except that the oxidation reaction time was 360 minutes. [Production Example 7] Oxidized cellulose G and CNF aqueous dispersion G were obtained by treating under the same conditions as in Production Example 1, except that the oxidation reaction temperature was 50°C. [Production Example 8] Oxidized cellulose H and CNF aqueous dispersion H were obtained by treating under the same conditions as in Production Example 1, except that the oxidation reaction time was 480 minutes.
[0067] The oxidized cellulose obtained in each production example was freeze-dried, and then the solid of the sample was left at 23°C and 50% RH for 24 hours or more. 13 As a result of measuring the C-NMR, it was confirmed that the second and third hydroxyl groups of the glucopyranose ring were oxidized to introduce carboxyl groups. 13 The measurement conditions for C-NMR are as follows. (1) Sample tube: Zirconia tube (4 mm diameter) (2) Magnetic field strength: 9.4T (1H resonance frequency: 400MHz) (3) MAS rotation speed: 15 kHz (4) Pulse sequence: CPMAS method (5) Contact time: 3 ms (6) Waiting time: 5 seconds (7) Number of times of accumulation: 10,000 to 15,000 times (8) Measuring device: JNM ECA-400 (manufactured by JEOL Ltd.) Furthermore, the fact that the oxidized cellulose obtained in each production example has a structure in which the second and third hydroxyl groups on the glucopyranose ring have been oxidized to introduce carboxyl groups was also confirmed by the results of measuring model molecules of the oxidized cellulose as samples. In addition, the sixth item concerns solid cellulosic raw materials. 13 C-NMR and solid state analysis of oxidized cellulose13 Since no change was observed in the spectral data with C-NMR, it was determined that the hydroxyl group at position 6 was not oxidized and remained as a hydroxyl group in the oxidized cellulose.
[0068] [Comparative Production Example 1] As a cellulose-based raw material, softwood pulp (Sigma-Aldrich, NIST RM 8495, bleached kraft pulp) was cut into 5 mm squares with scissors and processed at 25,000 rpm for 1 minute in an Osaka Chemical Wonder Blender WB-1 to mechanically defibrate the material into a cotton-like form. In a 100 ml beaker, 30.0 g of sodium hypochlorite pentahydrate crystals with an effective chlorine concentration of 43% by mass were placed, and pure water and 35% by mass of hydrochloric acid were added and stirred to obtain an aqueous solution with an effective chlorine concentration of 21% by mass and a pH of 11.0. This aqueous sodium hypochlorite solution was heated to 30°C in a thermostatic water bath while being stirred with a stirrer, and then 0.35 g of the mechanically defibrated softwood kraft pulp was added. After supplying the cellulose-based raw material, 48% by mass of sodium hydroxide was added to maintain the pH at 11.0 while keeping the temperature at 30°C in the same thermostatic water bath, and the mixture was stirred with a stirrer for 30 minutes. Next, the product was subjected to solid-liquid separation by suction filtration using a PTFE membrane filter with a mesh size of 0.1 μm to obtain oxidized cellulose P. The amount of carboxyl groups in the filtered product (oxidized cellulose P) obtained was measured after washing with pure water, and was found to be 0.42 mmol / g, and the amount of the filtered product was 0.31 g. The obtained oxidized cellulose P was dispersed in pure water to prepare a 0.1% dispersion, and a defibration process was carried out for 10 minutes using a Thinky Planetary Planetary Mixer "Awatori Rentaro ARE-310" in mix mode at a revolution speed of 2000 rpm and a rotation speed of 800 rpm, to obtain CNF aqueous dispersion P.
[0069] [Comparative Production Example 2] As a cellulose-based raw material, softwood pulp (Sigma-Aldrich, NIST RM 8495, bleached kraft pulp) was cut into 5 mm squares with scissors and processed at 25,000 rpm for 1 minute in an Osaka Chemical Wonder Blender WB-1 to mechanically defibrate the material into a cotton-like form. In a beaker, 30.3 g of sodium hypochlorite pentahydrate crystals with an effective chlorine concentration of 42% by mass were placed, and pure water was added and stirred to make the effective chlorine concentration 14% by mass. 35% by mass of hydrochloric acid was added thereto and stirred to make an aqueous solution with a pH of 9.0. This aqueous sodium hypochlorite solution was heated to 30°C in a constant temperature water bath while stirring with a stirrer, and then 0.35 g of the mechanically defibrated softwood kraft pulp was added. After supplying the cellulose-based raw material, the mixture was kept at 30°C in the same thermostatic water bath, and the pH during the reaction was adjusted to 9.0 while adding 48% by mass of sodium hydroxide, and the mixture was stirred with a stirrer for 30 minutes to carry out the oxidation reaction. After the reaction was completed, the product was subjected to solid-liquid separation by suction filtration using a PTFE mesh filter with a mesh size of 0.1 μm, and oxidized cellulose Q was obtained. 0.12 g of the filtered product obtained was washed with pure water. The amount of carboxy groups in the filtered product after washing (oxidized cellulose Q) was measured and found to be 1.12 mmol / g. Next, pure water was added to the oxidized cellulose Q to prepare a 0.1% dispersion, which was then subjected to a defibration treatment under the same conditions as in Comparative Production Example 1 to obtain a CNF aqueous dispersion Q.
[0070] [Comparative Production Example 3] As a cellulose-based raw material, softwood pulp (Sigma-Aldrich, NIST RM 8495, bleached kraft pulp) was cut into 5 mm squares with scissors and mechanically defibrated into a cotton-like form by processing at 25,000 rpm for 1 minute in a "Wonder Blender WB-1" manufactured by Osaka Chemical Co., Ltd. The mechanically defibrated cellulose fibers were dispersed in sufficient water and suction-filtered using a PTFE mesh filter with 0.1 μm openings to obtain a wet powder. The above wet powder (moisture content 80% by mass, 20 g in terms of dry powder) was placed in a container, and then ozone at a concentration of 200 g / m 360 L of ozone-oxygen mixed gas was added and shaken at 25°C for 2 minutes. After leaving it to stand for 6 hours, ozone and other substances were removed from the container, and the oxidized cellulose (oxidized cellulose R) was taken out and washed with pure water by suction filtration using a PTFE mesh filter with 0.1 μm openings. Pure water was added to the obtained oxidized cellulose R to prepare a 2 mass% dispersion, and sodium hydroxide was added to prepare a 0.3 mass% sodium hydroxide solution. After stirring for 5 minutes, the mixture was left to stand at 25°C for 30 minutes. Next, it was washed with pure water by suction filtration using a PTFE mesh filter with 0.1 μm openings. Pure water was added to the oxidized cellulose R to prepare a 0.1% dispersion, which was then defibrated under the same conditions as in Comparative Production Example 1 to obtain CNF aqueous dispersion R.
[0071] [Comparative Production Example 4] As a cellulose-based raw material, softwood pulp (Sigma-Aldrich, NIST RM 8495, bleached kraft pulp) was cut into 5 mm squares with scissors and processed at 25,000 rpm for 1 minute in an Osaka Chemical Wonder Blender WB-1 to mechanically defibrate the material into a cotton-like form. 4.92 g of sodium periodate was placed in a beaker, and pure water was added to make an aqueous solution (total volume 600 ml). This aqueous sodium periodate solution was heated to 55°C in a thermostatic water bath while being stirred at 200 rpm using a propeller-type stirring blade in a stirrer (Three-One Motor, BL600) manufactured by Shinto Scientific Co., Ltd., and then 6 g of the mechanically defibrated softwood kraft pulp was added. After the cellulosic raw material was supplied, the mixture was stirred under the same conditions for 3 hours using a stirrer while being kept at 55°C in the same thermostatic water bath. After the reaction was completed, the product was subjected to solid-liquid separation by suction filtration using a PTFE membrane filter with 0.1 μm openings to obtain oxidized cellulose S, which was then washed with pure water. Next, the product obtained above was added to a 1M aqueous acetic acid solution containing sodium chlorite, and stirred at 25°C for 48 hours under the same stirring conditions as above. After the reaction was completed, the product was subjected to solid-liquid separation by suction filtration using a PTFE membrane filter with a mesh size of 0.1 μm, and washed with pure water. Pure water was added to the obtained oxidized cellulose S to prepare a 0.1% dispersion, which was then defibrated under the same conditions as in Comparative Production Example 1 to obtain CNF aqueous dispersion S.
[0072] [Comparative Production Example 5] As a cellulose-based raw material, softwood pulp (Sigma-Aldrich, NIST RM 8495, bleached kraft pulp) was cut into 5 mm squares with scissors and processed at 25,000 rpm for 1 minute in an Osaka Chemical Wonder Blender WB-1 to mechanically defibrate the material into a cotton-like form. 0.016 g of TEMPO and 0.1 g of sodium bromide were placed in a beaker, and purified water was added and stirred to prepare an aqueous solution, to which 1.0 g of the mechanically defibrated softwood kraft pulp was added. The above aqueous solution is heated to 25°C in a thermostatic water bath while stirring with a stirrer, then 0.1M sodium hydroxide is added and stirred to obtain an aqueous solution of pH 10.0. 2.58g of an aqueous solution of sodium hypochlorite with an effective chlorine concentration of 13.2% by mass is added thereto, and while keeping the temperature at 25°C in the same thermostatic water bath, the pH during the reaction is adjusted to 10.0 while adding 0.1M sodium hydroxide, and stirring is performed with a stirrer for 120 minutes. After the reaction was completed, the product was subjected to solid-liquid separation by suction filtration using a PTFE membrane filter with 0.1 μm openings to obtain oxidized cellulose T. The obtained filtered material (oxidized cellulose T) was washed with pure water and then the amount of carboxy groups was measured. The amount of carboxy groups was 1.55 mmol / g, and the amount of the filtered material was approximately 1.0 g. Pure water was added to the obtained oxidized cellulose T to prepare a 0.1% dispersion, which was defibrated under the same conditions as in Comparative Production Example 1 to obtain CNF aqueous dispersion T. The nitrogen component derived from N-oxyl compounds in oxidized cellulose T was measured as the amount of nitrogen under the same conditions as in Production Example 1, and the increase from the raw pulp was calculated to be 5 ppm.
[0073] (2) Rating 1 [Examples 1-1 to 1-8, Comparative Examples 1-1 to 1-5] The following evaluations were carried out using the oxidized cellulose and CNF aqueous dispersions obtained in Production Examples 1 to 8 and Comparative Production Examples 1 to 5. The evaluation results are shown in Table 1.
[0074] [Measurement of Viscosity Average Degree of Polymerization] Oxidized cellulose was added to an aqueous solution of sodium borohydride adjusted to pH 10, and reduction treatment was carried out at 25°C for 5 hours. The amount of sodium borohydride was 0.1 g per 1 g of oxidized cellulose. After reduction treatment, solid-liquid separation was performed by suction filtration, washing with water, and the resulting oxidized cellulose was freeze-dried. 0.04 g of the dried oxidized cellulose was added to 10 ml of pure water and stirred for 2 minutes, after which 10 ml of 1 M copper ethylenediamine solution was added to dissolve it. The flow time of the blank solution and the flow time of the cellulose solution were then measured at 25°C using a capillary viscometer. The relative viscosity (η r ), specific viscosity (η sp ) and intrinsic viscosity ([η]) were measured sequentially, and the degree of polymerization (DP) of the oxidized cellulose was calculated using the viscosity measurement equation. η r =η / η0=t / t0 η sp = η r -1 [η]=η sp / (100×c(1+0.28η sp )) DP = 175 × [η]
[0075] [Measurement of average fiber width] Pure water was added to each of the CNF aqueous dispersions A-H, P-T obtained above to adjust the nanocellulose concentration in the CNF aqueous dispersion to 5 ppm. The CNF aqueous dispersions after the concentration adjustment were naturally dried on a mica substrate, and the nanocellulose shape was observed in AC mode using a scanning probe microscope "MFP-3D infinity" manufactured by Oxford Asylum. The average fiber width was calculated using the software provided with the "MFP-3D infinity" for more than 50 fibers, with the number average fiber width [nm] calculated as the cross-sectional height of the shape image = fiber width.
[0076] [Easy defibration] ○ Fiber defibration method A Each of the CNF aqueous dispersions A to H, P to T obtained above was placed in a 10 mm thick quartz cell, and the light transmittance at a wavelength of 660 nm was measured using a spectrophotometer (JASCO V-550). The solid content concentration of each CNF aqueous dispersion was 0.1 mass%. The higher the light transmittance, the better the defibration ability, as the CNF can be defibrated into sufficiently fine fibers even under mild conditions. The evaluation criteria are as follows (the same applies to defibration method B). ◎: Light transmittance is 80% or more ○: Light transmittance is 70% or more and less than 80% △: Light transmittance is 60% or more but less than 70% ×: Light transmittance is less than 60%
[0077] ○Defibration method B Each of the oxidized celluloses A-H, P-T obtained above was mixed with water to prepare an oxidized cellulose aqueous dispersion with a solid content adjusted to 0.1%. This oxidized cellulose aqueous dispersion was placed in a 13.5 ml glass container and treated for 10 minutes using a vortex mixer (VTX-3000L) manufactured by LMS to obtain a CNF aqueous dispersion. The solid content concentration of each CNF aqueous dispersion was 0.1% by mass. Each CNF aqueous dispersion was placed in a 10 mm thick quartz cell, and the light transmittance at a wavelength of 660 nm was measured using a spectrophotometer (JASCO V-550). Each measured value was evaluated on a four-point scale in the same manner as in defibration method A.
[0078] [Slurry Viscosity Stability] Aqueous slurries (50 g) containing 30 mass% titanium dioxide (Ishihara Sangyo Co., Ltd., R-820) and each of the CNF aqueous dispersions A to H, P to T were prepared by varying the amount of nanocellulose added so that the initial viscosity, which is the viscosity immediately after the slurry was prepared, was the same for each example (300 mPa s). A Thinky mixer, "Awatori Rentaro ARE-310" (mix mode, revolution: 2000 rpm, rotation: 800 rpm, 20 minutes) was used for mixing to prepare the aqueous slurries. The viscosity was measured immediately after preparation (initial viscosity) and after standing for one week. The viscosity change rate was calculated using the following formula, and the viscosity stability of the aqueous slurry was evaluated according to the following evaluation criteria. Viscosity change rate (%) = (N2 / N1) x 100 (In the formula, N1 is the initial viscosity of the slurry, and N2 is the viscosity of the slurry after the sample was left to stand for one week after preparation.) ◎: Viscosity change rate is less than 105% ○: Viscosity change rate is 105% or more but less than 110% △: Viscosity change rate is 110% or more but less than 115% ×: Viscosity change rate is 115% or more The samples were left to stand indoors at 23±2°C. The initial viscosity of the slurry and the viscosity after standing for one week were measured by stirring with a spatula at a speed not allowing bubbles to form, and then measuring the viscosity at 25°C, 100 rpm (shear rate 200 s) using a Toki Sangyo Co., Ltd. E-type viscometer (TV-22). -1 ) conditions were used for the measurements.
[0079] [Slurry handling properties] Aluminum silicate powder and water were added to each of the CNF aqueous dispersions A to H, P to T so that the aluminum silicate powder was 5 mass% and the nanocellulose was 0.5 mass%, and the mixture was stirred to prepare a processing liquid. After lightly stirring this processing liquid with a spatula, it was scooped up and visually observed for dripping when the spatula was tilted, and the slurry handleability was evaluated according to the following criteria. : When tilted, dripping occurred immediately. ○: Dripping occurred 5 seconds after tilting. △: Dripping occurred 10 seconds after tilting. ×: No dripping occurred even after 15 seconds.
[0080] [Surface condition after slurry coating (coatability)] Aluminum silicate powder and water were added to each of the CNF aqueous dispersions A to H, P to T so that the aluminum silicate powder was 5 mass% and the nanocellulose was 0.5 mass%, and the mixture was mixed and stirred to prepare a processing solution. The amount of aluminum silicate powder processed was 5 g / m 2 The processing solution was applied to a woven fabric (100% polyester, 100 mm x 100 mm) so that the processing solution was applied, and then dried. Ten pieces of the coated woven fabric were visually observed for uneven areas of the coating (processing unevenness) and evaluated according to the following criteria. ◎: No unevenness in processing was visible on any of the 10 sheets. ○: No unevenness in processing was observed on 8 to 9 sheets. △: No unevenness in processing was visible on 4 to 7 sheets. ×: No unevenness in processing was observed on 1 to 3 sheets, or unevenness in processing was observed on all 10 sheets.
[0081] [Table 1]
[0082] In Table 1, cases where no N-oxyl compound was used during the oxidation treatment of the cellulosic raw material (i.e., cases where the CNF dispersion contains substantially no N-oxyl compound) are represented by an "X", and cases where an N-oxyl compound was used (i.e., cases where the CNF dispersion contains an N-oxyl compound) are represented by an "O" (the same applies to Table 2).
[0083] The oxidized cellulose of Examples 1-1 to 1-8 easily disentangled cellulose microfibrils even with gentle stirring using a planetary centrifugal mixer or a vortex mixer, and showed high light transmittance when made into a CNF aqueous dispersion. Furthermore, defibration treatment using a planetary centrifugal mixer enabled the production of thin cellulose fibers with an average fiber width of 5 nm or less. Furthermore, the slurries of Examples 1-1 to 1-8 had a good balance of viscosity stability, handleability, and coatability. In particular, Examples 1-1 to 1-7, which had a degree of polymerization on the order of three digits, were evaluated as having excellent slurry properties, with viscosity stability, handleability, and coatability all being rated as "◎" or "○."
[0084] In contrast, in Comparative Examples 1-1 and 1-2, which have degrees of polymerization of 730 and 650, the cellulose microfibrils were difficult to disentangle with gentle stirring using a planetary mixer or a vortex mixer, and the defibration property was evaluated as "X". In addition, the slurry properties were all evaluated as "△", which was inferior to Examples 1-1 to 1-8. Comparative Examples 1-3 to 1-5, which used different oxidation methods, were also evaluated as inferior to the Examples in terms of defibration property and slurry properties.
[0085] (3) Rating 2 [Examples 2-1 to 2-11, Comparative Examples 2-1 to 2-5] [Easy defibration] Using the oxidized cellulose A-H, P-T obtained in each of Production Examples 1-8 and Comparative Production Examples 1-5, oxidized cellulose aqueous dispersions with oxidized cellulose concentrations of 0.1% (Examples 2-1, 2-2, 2-4, 2-6, 2-8-2-11, Comparative Examples 2-1-2-5) or 0.5% (Examples 2-3, 2-5, 2-7) were prepared. The oxidized cellulose aqueous dispersions were treated with a stirrer, and the resulting CNF aqueous dispersions were placed in 10 mm thick quartz cells and the light transmittance at a wavelength of 660 nm was measured using a spectrophotometer (JASCO V-550). For the CNF aqueous dispersions obtained by defibrating the 0.5% oxidized cellulose aqueous dispersions, the CNF aqueous dispersions were diluted with pure water to 0.1% and the light transmittance was measured. The mixer used was a Thinky Planetary Planetary Mixer, "Awatori Rentaro ARE-310," and the mixture was processed for 10 minutes in mix mode at a revolution speed of 2000 rpm and a rotation speed of 800 rpm. The evaluation criteria were as follows: ◎: Light transmittance is 80% or more ○: Light transmittance is 70% or more and less than 80% △: Light transmittance is 60% or more but less than 70% ×: Light transmittance is less than 60%
[0086] Using each CNF aqueous dispersion obtained by the defibration process in the above-mentioned defibration ease evaluation, the average fiber width, slurry viscosity stability, slurry handleability, and surface condition after slurry coating were measured and evaluated. The evaluation results are shown in Table 2 together with the amount of carboxyl groups in the oxidized cellulose used in the defibration process. The measurement and evaluation of the average fiber width, slurry viscosity stability, slurry handleability, and surface condition after slurry coating were performed in the same manner as in (2) above.
[0087] [Table 2]
[0088] The oxidized cellulose of Examples 2-1 to 2-11 easily disentangled cellulose microfibrils even with gentle stirring using a planetary centrifugal mixer, and showed high light transmittance when made into a CNF aqueous dispersion. Even when the oxidized cellulose concentration during defibration treatment was increased from 0.1% to 0.5%, the light transmittance of the CNF aqueous dispersion was sufficiently high, and the viscosity stability of the aqueous slurry, as well as the handleability and coatability, were well balanced.
[0089] In contrast, in Comparative Examples 2-1 to 2-5, when defibration was performed by gentle stirring using a planetary centrifugal mixer, the light transmittance of the CNF aqueous dispersions was low, at the 50% level. Furthermore, Comparative Examples 2-1 to 2-5 were also inferior to Examples 2-1 to 2-11 in terms of slurry properties.
Claims
1. An oxidized cellulose (excluding oxidized regenerated cellulose) containing a structure in which the second and third hydroxyl groups of the glucopyranose ring are oxidized to introduce a carboxyl group, the degree of polymerization of the oxidized cellulose is 600 or less, The light transmittance of the nanocellulose aqueous dispersion obtained by defibrating the aqueous dispersion of oxidized cellulose having a concentration of 0.1% by mass in a planetary centrifugal mixer at a revolution speed of 2000 rpm and a rotation speed of 800 rpm for 10 minutes is 60% or more; The amount of carboxy groups in the oxidized cellulose is 0.30 mmol / g or more. Oxidized cellulose.
2. 2. The oxidized cellulose of claim 1, wherein the oxidized cellulose is an oxidation of a cellulosic raw material with hypochlorous acid or a salt thereof.
3. 3. The oxidized cellulose according to claim 1 or 2, wherein the carboxyl group amount of the oxidized cellulose is 0.45 mmol / g or more.
4. An oxidized cellulose dispersion in which the oxidized cellulose according to any one of claims 1 to 3 is dispersed in a dispersion medium.
5. Nanocellulose obtained by defibrating the oxidized cellulose according to any one of claims 1 to 3 and having an average fiber width of 1 to 200 nm.
6. A nanocellulose dispersion in which the oxidized cellulose in the oxidized cellulose dispersion according to claim 4 is defibrated and has an average fiber width of 1 to 200 nm.
7. A nanocellulose dispersion in which the nanocellulose according to claim 5 is dispersed in a dispersion medium.
8. A cosmetic product in which the nanocellulose according to claim 5 or the nanocellulose dispersion according to claim 6 or 7 is used.
Citation Information
Patent Citations
JP1974034989A
Method for producing cellulose dispersion
JP2009161723A
Method for producing cellulose dispersion
JP2009161893A
Gas barrier material
JP2010156068A
Manufacturing method for oxidized cellulose, manufacturing method for oxidized cellulose dispersion liquid, and oxidized cellulose dispersion liquid
JP2011184475A
Cited By
Oxidized cellulose, nanocellulose and liquid dispersions thereof
JP2025066769A